2020
DOI: 10.1097/prs.0000000000006545
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Reduction Mammaplasty Offers Significantly Lower Costs with Comparable Outcomes: A Propensity Score–Matched Analysis of 18,780 Cases

Abstract: Background: Breast reduction mammaplasty is a common plastic surgery operation. Although many contemporary surgeons provide breast reduction mammaplasty as an outpatient procedure, roughly 15 percent of patients are still observed postoperatively. The authors hypothesize that observation confers no safety benefit but engenders significant cost. Methods: The authors reviewed cases of breast reduction mammaplasty in a commercial database and formulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…One drawback of using the NIS database for investigating bilateral reduction mammoplasty is the inability to capture mammoplasties performed as an outpatient procedure. 52 However, the majority of the study period draws patient data from a time where many reduction mammoplasties were performed in-patient, ensuring the capture of sufficient data and also records complications attributed to patient care, which is typically the residents’ responsibility. Given the necessity to explore the national scope of the duty hour restrictions, use of different databases such as the American College of Surgeons – National Surgical Quality Improvement Program (ACS-NSQIP) was not feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One drawback of using the NIS database for investigating bilateral reduction mammoplasty is the inability to capture mammoplasties performed as an outpatient procedure. 52 However, the majority of the study period draws patient data from a time where many reduction mammoplasties were performed in-patient, ensuring the capture of sufficient data and also records complications attributed to patient care, which is typically the residents’ responsibility. Given the necessity to explore the national scope of the duty hour restrictions, use of different databases such as the American College of Surgeons – National Surgical Quality Improvement Program (ACS-NSQIP) was not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…One drawback of using the NIS database for investigating bilateral reduction mammoplasty is the inability to capture mammoplasties performed as an outpatient procedure. 52 However, the majority of the study period draws patient data from a time where many reduction mammoplasties were performed in-patient, ensuring the capture of sufficient data and also records complications attributed to patient care, which is typically the residents' responsibility.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 Some studies have demonstrated a reduction in infection rates and surgical complications with outpatient surgery compared with inpatient surgery. 13,40 Previous authors have demonstrated success with breast reconstruction at ambulatory surgical centers. 41 These facilities can provide increased convenience and privacy for patients, which may be attractive to patients undergoing breast reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] One study revealed that reduction mammaplasty patients experienced fewer infectious complications when inpatient stays were avoided. 13 Few studies assess the outcomes of patients after prosthetic-based reconstruction with same-day discharge. This study aims to compare complication rates between inpatient and outpatient mastectomies with alloplastic reconstruction to determine whether same-day discharge is safe and feasible.…”
mentioning
confidence: 99%
“…The selection of a match ratio is based on several factors, including the statistical power and sample size needed for the study, the number of participants available for matching, and the ability to obtain optimal and similar distributions of propensity scores in each study group. Both types of matching are acceptable, though one-to-one matching (used in three of the six propensity score matching studies identified in this review) 8,9,11 can increase ease of statistical analysis and interpretability. However, 2:1 (or 3:1, etc.)…”
Section: Discussionmentioning
confidence: 99%